Study of electron energy distribution function and transport parameters for CF4, Ar gases mixture discharge by using the solution of Boltzmann equation-Part II - Radam, Hamid K. (Iraqi Journal of Physics, 2010)
The Boltzmann transport equation is solved by using two- terms approximation for pure gases and mixtures. This method of solution is used to calculate the electron energy distribution function and electric transport parameters were evaluated in the range of E/N varying from . 172152110./510.VcmENVcm The electron energy distribution function of CF4 gas is nearly Maxwellian at (1,2)Td, and when E/N increase the distribution function is non Maxwellian. Also, the mixtures are have different energy values depending on transport energy between electron and molecule through the collisions. Behavior of electrons transport parameters is nearly from the experimental results in references. The drift velocity of electron in carbon tetraflouride is large compared with other gases and mixtures. The mean electron energy to mixture is increasing at Argon ratios increased